Implementasi Stack pada Sistem Reservasi Restoran Berbasis Web dengan Stack-based History Management - Maria Winarni Br. Silitonga; Sahara Lani Lestari; Angelica Barus (CV. ITTC INDONESIA, 2025)
Web-based restaurant reservation systems are susceptible to user input errors that negatively affect operations and customer experience. This paper presents a prototype reservation application that integrates stack-based history management to provide Undo/Redo functionality, change tracking, and real-time reservation preview. The system is implemented with HTML, CSS, and JavaScript; history is managed using two stacks (undoStack and redoStack) implemented via JavaScript arrays, and LocalStorage is used for session persistence in the demo. Core operations (push/pop/peek) execute in O(1) time, ensuring responsive performance in small to medium-scale scenarios. Functional testing confirms the Undo/Redo behavior and improved error recovery and auditability. Limitations include large history memory usage and lack of multi-user synchronization; future work should explore backend persistence and synchronization techniques (e.g., CRDT or OT) for real-time collaborative support.